Yellow fever vaccination: should India have more centres? - Vikas Bhatia; Swayam Pragyan Parida (Wolters Kluwer Medknow Publications, 2015)
Yellow fever is endemic in rural areas of West Africa & South America and has never been reported in India. Except for the causative organism, all other factors responsible for transmission do exist in India. Case fatality rate is very high and there is no cure for Yellow Fever. Prevention through vaccination is the only available option to decrease morbidity & mortality. As per guidelines established by MoHFW, vaccination is mandatory for all travellers moving to or coming from YF endemic countries. Due to increase in international travel, a larger number of people from various parts of India require Yellow Fever vaccination and the demand will continue to increase in future. In India, there are only 27 locations in 10 states and 2 UTs which have the facility to vaccinate for Yellow Fever. People of many states have to cover a large distance for the vaccination. There is an urgent need to increase the number of sites. With the operationalization of various institutes under MoH&FW, there is an opportunity to create the network, closer to the potential travellers.